Analysis of the Dose-Response Effects of Physical Activity on Cardiocerebrovascular and All-Cause Mortality in Hypertension - Xu, Jun-Peng; Zeng, Rui-Xiang; Lu, Hai-Ning; Zhang, Yu-Zhuo; Mai, Xiao-Yi; Mao, Shuai; Zhang, Min-Zhou (Frontiers in Cardiovascular Medicine, 2022)
Background: Leisure-time moderate-to-vigorous physical activity (MV-PA) has been consistently regarded as a protective factor to prevent and treat hypertension. However, the effect of different levels of MV-PA against cardiocerebrovascular and all-cause mortality in hypertension is still unclear. The aim of this study was to explore the dose-relationships of MV-PA on these adverse outcomes in hypertension. Methods: In the National Health and Nutritional Examination Survey (NHANES) from 1999 to 2006, participants with hypertension were enrolled and classified into inactive (0 MET-h/week), low-active (0 < to < 7.5 MET-h/week) and high-active (≥ 7.5 MET-h/week) groups. Multivariate Cox regression was conducted with hazard ratio (HR) and corresponding 95% confidence interval (CI). To further explore the association between different levels of MV-PA and adverse outcomes, Kaplan-Meier survival curves, subgroup analysis and restricted cubic spline curves were performed. Results: During a median 10.93-year follow-up, 1,510 and 347 patients died from any causes and cardiocerebrovascular, respectively. High-active group had the highest event-free survivals of all outcomes compared to low-active and inactive groups. Multivariable Cox regression demonstrated that the high-active and low-active groups were both associated with reduced risks of all-cause [HR: 0.70, 95% CI: 0.60-0.82; 0.76 (0.68-0.86), respectively], and cardiocerebrovascular mortality [0.56 (0.41-0.77); 0.63 (0.50-0.81), respectively] compared to the inactive group. Subgroup analysis and restricted cubic spline curves showed that MV-PA surpassing 15 MET-h/week could decrease the risks of cardiovascular and all-cause mortality with inverse relationships, which was not the case for cerebrovascular mortality, indicating a U-shaped association. Conclusions: Our study suggests that highly active MV-PA of 7.5 to < 15 MET-h/week was associated with the lowest risks of cardiocerebrovascular and all-cause mortality in hypertension.